Konflik Kepemilikan Tanah antara Kawasan Hutan dan Permukiman Masyarakat dalam Perspektif Sosiologi Hukum - Muhammad Fazrin; Kms. Novyar Satriawan Fikri; Bambang Sasmita Adi Putra (MAN 4 Kota Pekanbaru, 2026)
Indonesia, as a constitutional state (rechtsstaat), requires agrarian and forestry governance to be based on legal frameworks that promote public welfare. Nevertheless, overlaps between designated forest areas and long-established community settlements remain common, including in Indragiri Hilir Regency. This study aims to identify the forms of land tenure conflicts between forest areas and community settlements, examine their underlying causes, and analyze conflict resolution from a legal sociology perspective. The research employs a normative legal method using statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials collected through library research and analyzed descriptively. The findings reveal three forms of conflict: overlapping legal status, horizontal and vertical disputes, and tensions between formal legality and social legitimacy. These conflicts are driven by weak regulatory and institutional capacity, limited public participation and policy communication, and socio-historical patterns of land tenure. Effective resolution requires integrating formal legal mechanisms with sociological and mediation-based approaches that recognize customary institutions. Strengthening inter-agency coordination and land data synchronization is essential to achieving legal certainty and social justice.